Lenvatinib Combined With a PD-1 Inhibitor as Effective Therapy for Advanced Intrahepatic Cholangiocarcinoma - Xie, Lulu; Huang, Jingzheng; Wang, Linling; Ren, Wenrui; Tian, Hao; Hu, Anhong; Liang, Jun; Jiao, Yuqing; Li, Yali; Zhou, Qunfang; Zhang, Wenjing (Frontiers in Pharmacology, 2022)
Background: The combined treatment of Lenvatinib with PD-1 inhibitor has obtained satisfactory antitumor effect in several solid tumors. However, the efficacy and tumor response of Lenvatinib plus PD-1 inhibitor in advanced intrahepatic cholangiocarcinoma (ICC) still needs further exploration. Methods: This is a single-arm study for assessment of the efficacy and tolerability of Lenvatinib plus PD-1 inhibitor in ICC patients who had chemotherapy failure. Efficacy was evaluated based on the Response Evaluation Criteria in Solid Tumors RECIST Version 1.1 (RECIST 1.1). Results: Total of 40 patients with advanced ICC were enrolled after chemotherapy refractory. Median progression-free survival ( PFS) was 5.83±0.76 months. The 3-month, 6-month PFS rates were 80%, 32.5%. Median overall survival ( OS) was 14.30±1.30 months. The 12-month, 18-month rates were 61.4%, 34.7%. The 3-month RECIST 1.1 evaluation was that 7 patients (17.5%) showed partial response (PR), 23 patients (57.5%) had stable disease (SD), 10 patients (25.0%) had progressive disease (PD). Objective response rate (ORR) was 17.5%, and Disease control rate (DCR) was 75.0%. All the recorded any-grade adverse events (AEs) inducing treatment termination were controllable, and there were no AEs-related deaths. Conclusions: Our study showed that combination of Lenvatinib with PD-1 inhibitor could be as effective treatment for ICC after chemotherapy refractory. Further trials are required to investigate this treatment for advanced ICC.